2000
DOI: 10.1002/1097-0185(20001101)260:3<213::aid-ar10>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and death in the gastric epithelium of developing rats after glucocorticoid treatments

Abstract: Glucocorticoids take part in the intense morphofunctional modifications that occur in the gastric mucosa during fetal and postnatal development. Two studies were designed to evaluate corticoids role in gastric cell proliferation and apoptosis in developing rats: in vivo, using suckling animals; in vitro, using gastric explants obtained from 20‐day fetuses. These explants were cultured in DMEM/F12 medium treated or not with 50 ng/ml of corticosterone; after 22 hr, vincristine was added to the medium for 2 hr to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(51 reference statements)
2
12
0
Order By: Relevance
“…The entire digestive epithelium would thus be fully replaced every month (25 days) and the period of time required for the complete replacement of the epithelium of alveolotubular units in the digestive gland of mussels would be irreconcilable with previous reports that have presumed a massive renovation of the digestive epithelium every feeding cycle, viz., twice per day in intertidal mussels (Nelson and Morton 1979). In human colorectal mucosa, the average BrdU labelling index is 77‰-110‰ (Potten et al 1992), whereas in rat gastric epithelium, it is around 150‰ (Gama et al 2000). These BrdU labelling values seem to be maximum threshold values in normal nonglandular epithelia (Bertalanffy 1962;Humme and Potten 1980;Potten et al 1992;Pawlinoski et al 1999;Gama et al 2000) and are comparable with those that we have found here in stomach epithelium.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The entire digestive epithelium would thus be fully replaced every month (25 days) and the period of time required for the complete replacement of the epithelium of alveolotubular units in the digestive gland of mussels would be irreconcilable with previous reports that have presumed a massive renovation of the digestive epithelium every feeding cycle, viz., twice per day in intertidal mussels (Nelson and Morton 1979). In human colorectal mucosa, the average BrdU labelling index is 77‰-110‰ (Potten et al 1992), whereas in rat gastric epithelium, it is around 150‰ (Gama et al 2000). These BrdU labelling values seem to be maximum threshold values in normal nonglandular epithelia (Bertalanffy 1962;Humme and Potten 1980;Potten et al 1992;Pawlinoski et al 1999;Gama et al 2000) and are comparable with those that we have found here in stomach epithelium.…”
Section: Discussionsupporting
confidence: 87%
“…In human colorectal mucosa, the average BrdU labelling index is 77‰-110‰ (Potten et al 1992), whereas in rat gastric epithelium, it is around 150‰ (Gama et al 2000). These BrdU labelling values seem to be maximum threshold values in normal nonglandular epithelia (Bertalanffy 1962;Humme and Potten 1980;Potten et al 1992;Pawlinoski et al 1999;Gama et al 2000) and are comparable with those that we have found here in stomach epithelium. Based on similar calculations to those reported above for digestive alveolar units, the entire renewal of duct and stomach epithelia has been concluded to last 6 months (175 days) and 3 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelium has a high turnover rate that necessitates the apoptotic removal of cells at the end of their normal life cycle (2). In neonatal rats, the exposure to stress results in increased apoptosis in the gastric (20) and the intestinal epithelium (33). In vitro studies using the rat intestinal epithelial cell line IEC-6 demonstrated a dose-dependent effect of increasing corticosteroid levels on the induction of apoptosis (34).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to stress can result in increased epithelial apoptosis of the gastrointestinal tract (20,33). To characterize animal response to repeated asphyxia/cold stress during the study, plasma corticosterone levels were measured using RIA.…”
Section: Morphometric Measurementsmentioning
confidence: 97%
“…The direct effect of S. stercoralis on the small bowel mucosa can be related to the secreted ecdysteroids as discussed by Genta (42) and identified in other parasitic helminths (43). This hormone is structurally similar to some metabolites of human steroids (44) from which corticosteroids are known to induce apoptosis concomitant with inhibition of cell proliferation (45,46).…”
Section: Discussionmentioning
confidence: 99%